Principal's Strategy in Developing Al-Qur'an Learning in Madrasah Tsanawiyah - Mukhammad Yusuf Ro’is; Mauhibur Rokhman (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2021)
The purpose of this article is to explain and analyze the Qur'anic learning process and the principal's strategy in developing Qur'anic learning at MTs Sunan Giri in Probolinggo. This article uses a qualitative research type with a case study approach. The research site is at MTs Sunan Giri Probolinggo. The information for this research is the principal of the madrasa, the deputy head of the madrasa, the teacher concerned, and the students. This research was conducted from January to May 2021. The results of this article are: 1) The process of learning the Koran is carried out in learning and extracurricular activities. 2) the strategies carried out by the principal are: The strategy of the principal of MTs Sunan Giri Probolinggo City in developing Al-Qur'an learning in his school there are several roles, namely: 1) the principal acts as an educator (educator), 2) the principal acts as a manager, 3) the principal acts as an administrator, 4) the principal acts as a supervisor, 4) the principal acts as a leader, 5) the principal acts as an innovator, 6) the principal acts as a motivator, 6) the principal acts as an innovator and facilitator.